Hydrochlorothiazide-induced glucose metabolism disorder is mediated by the gut microbiota via LPS-TLR4-related macrophage polarization - Jian-Quan Luo; Huan Ren; Man-Yun Chen; Qing Zhao; Nian Yang; Qian Liu; Yong-Chao Gao; Hong-Hao Zhou; Wei-Hua Huang; Wei Zhang (iScience, 2023)
Summary: Hydrochlorothiazide (HCTZ) is reported to impair glucose tolerance and may induce new onset of diabetes, but the pharmacomicrobiomics of the adverse effect for HCTZ remains unknown. Mice-fed HCTZ exhibited insulin resistance and impaired glucose tolerance. By using FMT and antibiotic cocktail models, we found that HCTZ-induced metabolic disorder was mediated by commensal microbiota. HCTZ consumption disturbed the structure of the intestinal microbiota, causing abnormal elevation of Gram-negative Enterobacteriaceae and lipopolysaccharide (LPS) then leading to intestinal barrier dysfunction. Additionally, HCTZ activated TLR4 signaling and induced macrophage polarization and inflammation in the liver. Furthermore, HCTZ-induced macrophage polarization and metabolic disorder were abrogated by blocking TLR4 signaling. HCTZ consumption caused a significant increase in Gram-negative Enterobacteriaceae, which elevated the levels of LPS, thereby activating LPS/TLR4 pathway, promoting inflammation and macrophage polarization, and resulting in metabolic disorders. These findings revealed that the gut microbiome is the key medium underlying HCTZ-induced metabolic disorder.